Methodologies of Verbal autopsy and Social autopsy tools, adopted by VASA studies in exploring under-five mortality determinants - Muhammad Bilal Siddiqui; Chiu Wan Ng; Wah Yun Low (International Journal of Endorsing Health Science Research, 2018)
Background: Verbal Autopsy/Social Autopsy (VASA) tools should be based on a well-holistic conceptual framework, allowing them to record and organize a wide range of determinants and contributors of child mortality in developing countries. This paper aims to review how successfully VASA studies have been able to record and organize biological and social determinants of child mortality, in pursuit of World Health Organization’s (WHO) guidelines for verbal autopsy (VA) and Kalter’s recommendations for social autopsy (SA).